Analisis Strategi Memasuki Pasar Internasional - Putri Ramadhani, Nuri Aslami (Journal Economy and Currency Study (JECS), 2022)
The purpose of this study is to find out the motive for "going International SGMW, the Market Entry Mode chosen by SGMW, the reason for SGMW choosing Indonesia as its production base and knowing the segmentation, targeting, positioning and branding marketing strategies applied by SGMW in Indonesia. The data analysis method used is descriptive analysis with a qualitative approach using SWOT analysis and SWOT matrix. The results showed that the strategy applied by Wuling Motors in entering the international market was to apply the Aggressive strategy. From the results of data analysis with the SWOT matrix, it can be seen that Wuling Motors has higher strengths than weaknesses. From the results of data analysis with the SWOT matrix, it can be seen that opportunities are higher than threats. Based on these results, the appropriate strategy to be applied to Wuling Motors is the Wuling Motors Aggressive Strategy by conducting market penetration, market development and product development.